HUMAN TRAFFICKING DALAM PERSEPTIF HUKUM INTERNASIONAL - Ketut Arbi Krisna Dwipayana (Jurnal Komunikasi Hukum, 2025)
Human trafficking is a complex and organized transnational crime that involves serious violations of Human Rights. This crime treats humans as commodities that can be traded for economic gain, thus ignoring human dignity and worth. From an international legal perspective, various instruments have been agreed to combat this crime, such as the 2000 Palermo Protocol, the Universal Declaration of Human Rights, the Civil and Political Covenant, and CEDAW which emphasizes the protection of women. Although there have been global efforts to encourage the eradication of human trafficking, this practice continues to grow due to factors such as poverty, gender inequality, low education, and weak law enforcement at the national level. This study uses a normative legal approach, by examining the applicable international legal instruments and how they are implemented in Indonesia. Indonesia itself has ratified several international legal instruments and stipulated them in national regulations such as Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking. The results of the study show that although legally there is a strong legal umbrella, challenges still arise in terms of coordination between institutions, suboptimal victim protection, and low deterrent effects for perpetrators. Therefore, it is necessary to strengthen international cooperation, consistent law enforcement, and community empowerment in preventing human trafficking.